The supports and challenges of political Islam during reformation Indonesia - Gonda Yumitro; Elfatih Abdullahi Abdelsalam; Syaza Farhana Mohamad Shukri (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2021)
This article aims to elaborate and describe the supports and challenges towards the development of political Islam during reformation Indonesia. This qualitative research used literature reviews methods of data collection. After validating and removing irrelevant data, the collected data were analyzed using Nvivo 12 Plus as an analysis tool. The authors found that some supports of political Islam during reformation Indonesia are the emergence of Islamic groups supporting Islamic law, Islamic values in various fields, and the favorable Islamic pop culture. On the other hand, the challenges of political Islam are in the form of the anti-Islamization movements and the issues of Islamic terrorism. Moreover, the supports for the existence of actors bringing the ideas of political Islam developed significantly in the era of President Habibie, which was the earlier phase of changing from the Suharto authoritarian regime, for instance, by the emergence of various Islamic political movements. However, the development has steadily declined following the increasing challenges towards political Islam during reformation Indonesia, especially since the second era of Presidents Susilo Bambang Yudhoyono (SBY) and President Joko Widodo (Jokowi) government, such as by the emergence of the anti-Islamization movement and the issue of Islamic terrorism. In the future, the field research through survey and interview is expected to validate the findings of this article.